Pengembangan Profesionalitas Guru Pendidikan Pancasila dan Kewarganegaraan Melalui Tindakan Reflektif - Saadah, Khilma Azis Wakhidatus (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2022)
This study aimed to describe the process, the effort, and the benefits of reflective actions of Pancasila and Civic Education teachers in developing professional competencies. The research utilized a qualitative approach with phenomenology—the data was collected through observation, interviews, and documentation. Reflection activities should be carried out by the teacher continuously with learning. The benefits of reflection activities carried out by teachers were knowing problems when planning, implementing, assessing, guiding, and educating, as well as carrying out additional tasks. Efforts to improve the professional competence of teachers were conducting classroom action research and improving skills along with the times. Professional teachers should carry out classroom action research to improve the learning process in the classroom, career support, and new knowledge about scientific work. Teachers were required to keep up with the times by learning from various sources to utilize technology to increase students' learning activeness.